66 Long-term survival and neurodevelopmental outcomes of very-preterm infants born in Canada between 2009 and 2016. (29th October 2021) - Ricci, M Florencia; Shah, Prakesh; Moddemann, Diane; Alvaro, Ruben; Ng, Eugene; Lee, Shoo K; Synnes, Anne
Abstract: Primary Subject area: Neonatal-Perinatal Medicine Background: Quality improvement programs across Canadian Neonatal Network (CNN) sites have led to increased neonatal survival without major neonatal morbidity among infants born extremely preterm. The next step is to determine if such activities impact longer-term survival and neurodevelopmental outcomes. Objectives: This cohort study aimed to compare death or significant neurodevelopmental impairment (sNDI) (Bayley-III scores < 70, severe cerebral palsy, blind, or hearing aided) at 18-24 months corrected age among infants born < 29 weeks' gestation admitted to CNN sites, between 2 Epochs: 1 (2009-2012) and 2 (2013-2016). Secondary objectives included death or neurodevelopmental impairment (NDI) (Bayley-III < 85, any cerebral palsy, visual or hearing impairment), death, sNDI, NDI, and components of neurodevelopmental impairment. Design/Methods: Only sites with ≥ 70% follow-up rates were included. Differences in maternal-infant characteristics and neonatal morbidities were assessed by Pearson Chi-square and Student t-test testing. Adjusted odds ratios with 95% CIs were calculated for outcome change between the 2 Epochs, accounting for patient characteristic differences in the model. Results: Study population included 4426 children; Epoch 1: 1895 (43%) and Epoch 2: 2531 (57%). In Epoch 2, more mothers received MgSO4 (56.3% vs. 28.4%; p<0.01), antibiotics (69%vs.65.3%; p 0.01) and delayed cord clamping (37.1% vs. 31.3%; p 0.02), and fewer infants had SNAP-2 (illness severity score) >20 (30.7% vs. 35.2%; p<0.01) or late-onset sepsis (23.3% vs. 26.9%; p 0.01). See Table 1. Conclusion: Significant reductions in rate of death or sNDI, and in visual and hearing impairment, were identified between Epoch 2 to Epoch 1. An increase in poor cognitive outcome rates requires further study.